SEISMIC SIGNAL ENHANCEMENT USING EMPIRICAL WAVELET TRANSFORM - LEE, WEI YI (2020)
Seismic noise is unwanted energy which opposed to the signals corresponding to the reflected energy from the subsurface features, and it affects the quality of the seismic subsurface image. Hence, the seismic noise attenuation is one of the procedures in seismic pre-processing to remove or attenuate most of the seismic noise. Fourier Transform (FT) is among the earliest approach used in seismic noise attenuation, however the limitations regarding the poor separation between signal and noise results in signals attenuation. Therefore, seismic noise attenuation using time-frequency analysis (Short Time Fourier Transform (STFT) and Wavelet Transform (WT)) gives better isolation between primary signal and noise as it provides time and frequency information simultaneously.